The Ethics of Non-Therapeutic Male Circumcision Under Islamic Law - Dabbagh, Hossein (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract This qualitative research is a philosophical review about analyzing how circumcision can (cannot) be morally justified. It is typically assumed among Muslims that circumcision is mandatory according to Islamic law (Sharia). However, in this paper, I will argue that this is not clear in Islamic texts. Because firstly there is no textual evidence in the Quran about this matter and secondly permissibility of circumcision is not an agreed topic among Muslim scholars. This entails that circumcision is not a necessary part of being a Muslim. Although this idea seems idiosyncratic according to the majority of Muslims, I’m inclined to emphasize that we should not marginalize this idea, rather we have to support it for educational prosperity in Muslim communities. But perhaps more importantly this paper helps to introduce new Muslim intellectuals’ argument that moral reasoning is independent from (and even superior to) Islamic law. Since we do not have ultimate and decisive secular reason (e.g., medical reason) against male circumcision in every occasion, therefore, morally speaking, I believe it is not reasonable to say that male circumcision is always wrong. Muslims who support male circumcision still can find some secular reasons to defend this from their cultural identity. Abstrak Penelitian kualitatif ini merupakan tinjauan filosofis yang bertujuan menganalisis bagaimana sunat dapat atau tidak dapat dibenarkan secara moral. Ummat Muslim beranggapan bahwa hukum sunat adalah wajib menurut hukum Islam (Syariah). Akan tetapi, dalam tulisan ini, saya akan berargumen bahwa belum ada penjabaran yang pasti perihal asal hukum wajib pada sunat ini dalam Islam. Argumen ini memiliki dua alasan. Alasan pertama adalah tidak ada bukti tertulis dalam Al Qur'an tentang asal hukum wajib sunat ini dan alasan kedua adalah pembolehan sunat bukanlah topik yang disepakati di antara para cendikia Muslim. Atas dasar tersebut, keadaan yang mensyaratkan seseorang untuk sunat bukanlah hal yang wajib untuk menjadi seorang Muslim. Meskipun gagasan ini tampaknya idiosynkratik menurut mayoritas umat Muslim, saya menekankan bahwa kita tidak boleh menyisihkan gagasan ini, tetapi kita harus mendukungnya untuk kemakmuran pendidikan di komunitas Muslim. Kendati demikian mungkin yang lebih penting lagi bahwa tulisan ini membantu untuk memperkenalkan argumen intelektual Muslim yang baru bahwa penalaran moral adalah independen dari (dan bahkan lebih tinggi dari) hukum Islam. Karena kita tidak memiliki alasan kuat dan alasan sekuler (seperti alasan medis) terhadap sunat pada laki-laki didalam setiap keadaan. Kendati demikian, secara moral, saya percaya bahwa tidak beralasan untuk mengatakan bahwa sunat laki-laki itu selalu salah. Muslim yang mendukung sunat pada laki-laki masih dapat dilakukan dengan menemukan beberapa alasan sekuler untuk mempertahankan kegiatan sunat dari identitas budaya ummat muslim. How to Cite : Dabbagh, H. (2017). The Ethics Of Non-Therapeutic Male Circumcision Under Islamic Law: A Lesson For Educational Prosperity In Muslim Communities . TARBIYA: Journal of Education in Muslim Society, 4(2), 216-223. doi:10.15408/tjems.v4i2.6017. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.6017